ANALYSIS OF MARKETING ASPECTS IN SPORT TOURISM ( CASE STUDY ON PEGASUS STABLE) - Nova Sitorus (JELAJAH: Journal of Tourism and Hospitality, 2021)
One of the tourism sectors that continues to grow is Sports Tourism. Sports Tourism is a form of special interest tourism that has participation, or watching sports as its main component / theme / motivation of the trip. This includes all forms of active and passive involvement in sporting activities, participating regularly or in an organizational manner for non-commercial or commercial reasons, which necessitates traveling away from home and working there. Sports Tourism is one of the fastest growing sub-sectors in special interest tourism. The aim is to promote tourist destinations through a variety of sports activities, both indoor and outdoor. This research aims to find out how to identify the tourism component in Pegasus Stable and to find out how to analyze marketing in Pegasus Stable. Based on the problems to be studied, the research team chose to use qualitative research methods. The data collection technique that will be carried out is interviews. Pegasus Stable carries out a marketing strategy by determining market segmentation, namely through the income level of its target market and positioning itself according to the intended target market, such as positioning, namely the reputation of Pegasus Stable which automatically proves their high standards, because many ASEAN Games & SEA Games participants came from training facilitated by Pegasus Stable. Pegasus Stable also looked at the components of the marketing mix (8P) and adjusted accordingly. Starting from Products, providing facilities for riding, both for schools, photoshoots, horse care and rentals arena. Price , Pegasus Stable set a fairly affordable price compared to competitors. Location, which is easy to access. Promotion through social media, direct approach and word of mouth. Packaging provides attractive tour packages that are packaged at affordable prices, so that they are profitable and attract the attention of ordinary tourists and special tourists. Programming by holding an annual event that tourists look forward to specifically to maintain communication between horse riders. Cooperation, the existence of cooperation with the government and foreign parties. And finally, in human resources, there are human resources with the best quality through an appropriate recruitment process and evaluation process that is carried out regularly. Keyword: marketing, sport tourism, analysis